HIV and the eye - Gichuhi, Stephen; Arunga, Simon (HIV, 2020)
The main ocular effects of HIV are related to immune suppression and impaired immune surveillance of tumours. HIV compromises cell-mediated immunity, thereby increasing the risk of infection with: • bacteria (e.g., those causing tuberculosis and syphilis) • fungi (e.g., Candida spp. and Cryptococcus spp.) • parasites (e.g., Toxoplasma gondii) • viruses (e.g., herpes zoster virus, human papillomavirus, Kaposi sarcoma-associated herpes virus, cytomegalovirus and Epstein-Barr virus). Patients with lower CD4 counts are more likely to have ocular manifestations1; however, use of antiretroviral therapy (ART) has modified the epidemiology of ocular manifestations and variations in the predominant subtype of HIV may also lead to geographical differences in eye disease.
Keywords: HIV; Eye